Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1242/dev.185009
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of chromatin accessibility by the conserved transcription factor Grainy head is developmentally regulated

Abstract: The dramatic changes in gene expression required for development necessitate the establishment of cis-regulatory modules defined by regions of accessible chromatin. Pioneer transcription factors have the unique property of binding closed chromatin and facilitating the establishment of these accessible regions. Nonetheless, much of how pioneer transcription factors coordinate changes in chromatin accessibility during development remains unknown. To determine whether pioneer-factor function is intrinsic to the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 104 publications
(205 reference statements)
1
14
2
Order By: Relevance
“…DESeq2 with an adjusted p-value < 0.05 and a fold change > 2 as thresholds for differential accessibility. Previously published ATAC-seq datasets (Hannon et al 2017), GSE86966; (Blythe and Wieschaus 2016), GSE83851; (Nevil et al 2020), GSE137075. were re-analyzed in parallel with ATAC-seq data from this study to ensure identical processing of data sets.…”
Section: Atac-seq Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…DESeq2 with an adjusted p-value < 0.05 and a fold change > 2 as thresholds for differential accessibility. Previously published ATAC-seq datasets (Hannon et al 2017), GSE86966; (Blythe and Wieschaus 2016), GSE83851; (Nevil et al 2020), GSE137075. were re-analyzed in parallel with ATAC-seq data from this study to ensure identical processing of data sets.…”
Section: Atac-seq Analysismentioning
confidence: 99%
“…2016. ATAC-seq data for stage 5 embryos is fromNevil et al 2020. Region highlighted in green indicates the GAF-dependent, GAFbound Ubx promoter.…”
mentioning
confidence: 99%
“…This correlation between Zld binding and open chromatin was similar to the previously reported association between Zld-bound regions and chromatin accessibility in the early embryo (Harrison et al, 2011). To better understand this relationship between accessibility and Zld binding, we used recently published ATAC-seq data generated in stage 5 embryos (Nevil et al, 2020) to allow us to compare accessibility and Zld binding in both the embryo and type II neuroblasts. This analysis showed that while Zld-bound loci and regions of open chromatin differ between the two cell types, there is a correlation between binding and accessibility in both (Figure 5A, Figure S5C).…”
Section: Resultsmentioning
confidence: 99%
“…This was later supported by Jacobs et al 2018 (Blastyak et al, 2006, Tuckfield et al, 2002 further illustrating the ability of Grh to recruit co-factors to confer its activator or repressive functions. Grh's pioneer factor activity appears to be regulated temporally with Grh pioneer factor activity required during late embryonic development but not during early embryonic development (Nevil et al, 2020), thus whether Grh is acting as a pioneer factor or directly activating or repressing genes in the intestine requires further investigation.…”
Section: Discussionmentioning
confidence: 99%